Criteria for the selection of phosphobacteria - Ramos Cormenzana, R. (Ars Pharmaceutica (Internet), 1970)
On exposed criteria for phosphobacteria selection. These criteria are base on managing of the cultures on dicalcium phosphate and calcium glycerophosphate plate solubilization and on the use of sodium glycerophosphate as the exclusive source of phosphorous. The evaluation of the selected microorganisms according to phosphorus release on cluture media was satisfactory.